OCCURRENCE OF THIRAM ECTOPARASITICIDE IN ANIMAL FEED STUFF(S) - R. Kavitha; R.P. Senthilkumar; A. Natarajan; T.K. Sundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Thiram (tetramethylthiuram disulphide) is a common ectoparaciticide, used post harvest in cereal, cotton and soybean seeds to protect them from fungal attack and retain germination potential. The seeds treated with thiram sporadically gain entry into animal feed manufacturing and its toxicity is observed in poultry and animals. The occurrence of thiram in various feed ingredients and in feeds was investigated. A total of 636 samples of feed ingredients and feeds were analysed for thiram qualitatively.Among the cereals analysed jowar showed presence of thiram in 5 out of 95 samples analysed followed by bajra in 3 out of 256 samples. While only one maize sample was found to be contaminated with thiram out of 213 samples, the rest of the ingredients were found to be negative for thiram traces. The presence of thiram, though in small number of ingredients, indicates that the ingredients, especially cereals treated with thiram, occasionally gain entry into animal /bird feeding. There should be a quality assurance programme in every intensive feed manufacturing unit as a routine basis to detect thiram contamination in feed ingredients to prevent serious damage to the health and productivity of animals / poultry.